PENINGKATAN KEMAMPUAN BELAJAR PENDAPATAN NASIONAL DENGAN KOMIK EKONOMI PADA SISWA KELAS X SMA N 1 MRANGGEN - Ani, Risa Ari (Dinamika Pendidikan, 2012)
The objective of the study was to determine the use of the economics comic medium on the basic competence of national income. This medium was selected since students faced difficulty to understand the concept of the economics. The study took place in SMAN 1 Demak, Mranggen. The subjects were 36 students of X-4 class on the 2nd semester in the academic year of 2011/2012. It was a Classroom Action Research conducted in two cycles. The result of the 1st cycle showed that the average of studentsâ€™ learning outcomes was 71 with classical achievement was 69%, so it increased up to 33% comparing to the initial conditions. In the 2nd cycle, the average of studentsâ€™ learning outcomes was 74 with classical achievement was 86%, it rose by 17% which was better comparing to the 1st cycle.Â